2002
DOI: 10.1007/s00134-001-1199-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of interleukin-6 to interleukin-10 ratio in chronic alcoholics: association with postoperative infections

Abstract: Chronic alcoholics had decreased IL-6/IL-10 ratios at ICU admission and increased rates of infectious complications in the postoperative ICU course. This may indicate immediate postoperative immune suppression before the onset of infections and may help to identify chronic alcoholic patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 41 publications
4
47
0
6
Order By: Relevance
“…This inability to elicit a strong primary response may result in the bacterium not being cleared effectively from the bloodstream. Our results are consistent with those of Sander et al (38), who recently reported that suppressed IL-6/IL-10 ratios were associated with increased susceptibility to postoperative infections in chronic alcoholics compared to that in nonalcoholics.…”
supporting
confidence: 93%
“…This inability to elicit a strong primary response may result in the bacterium not being cleared effectively from the bloodstream. Our results are consistent with those of Sander et al (38), who recently reported that suppressed IL-6/IL-10 ratios were associated with increased susceptibility to postoperative infections in chronic alcoholics compared to that in nonalcoholics.…”
supporting
confidence: 93%
“…In addition, chronic alcoholic patients undergoing cardiac and gastric surgery have a higher level of the anti-inflammatory cytokine IL-10, as well as a lower ratio of pro-inflammatory IL-6 to antiinflammatory IL-10. These changes are associated with a marked increase in the infection rate after surgery (Sander et al 2002). Few studies have examined the association between ALD and inflammation; thus, the factors underlying this association remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Proinfl ammatory cytokine production is decreased, and studies have demonstrated decreased levels of IL-1, IL-6, IL-12, tumor necrosis factor-a , and interferon-g . 45,73,81 Antiinfl ammatory cytokine concentrations of IL-10 also are decreased. Stress induced by trauma or surgery results in a production of proinfl ammatory cytokines and, in the normal host, is compensated by an antiinfl ammatory response.…”
Section: Surgical Patientsmentioning
confidence: 99%